Balancing cognitive complexity and gaming level: Effects of a cognitive complexity-based competition game on EFL students' English vocabulary learning performance, anxiety and behaviors. (April 2020) - Yang, Qi-Fan; Chang, Shao-Chen; Hwang, Gwo-Jen; Zou, Di
Abstract: Digital game-based language learning promotes motivation and enables learners to immerse themselves in learning. However, some gaming elements (e.g., competition and challenge) or learning content (e.g., difficulty levels) may have different influences on different learners, especially those with low self-efficacy or academic achievement, as competitive games may lead to frustration. It is therefore important to take students' cognitive capacities into consideration when designing a competitive learning environment, and to provide them with learning content of appropriate cognitive complexity. In the current study, a game-based situational vocabulary learning system that integrated a cognitive complexity-based competition strategy was developed to provide learners with appropriate tasks. A quasi-experiment was conducted in a high school English course to evaluate the effectiveness of the proposed approach. It was found that, compared to the conventional situational gaming approach, the situational game with the cognitive complexity-based competition strategy significantly improved the participants' learning performance (in particular, that of the low-achieving students), but it also increased their anxiety. Furthermore, the behavioral analysis showed that the students who learned with the proposed approach accomplished the tasks more smoothly, because the system could take into account players' learning performance and adjust the cognitive complexity of the following tasks through upgrading or downgrading the learners' gaming levels to ensure that individual students learned with tasks at appropriate levels for them. On the other hand, the participants who learned with the conventional game-based learning approach had a greater tendency to fail the game repeatedly. Based on the findings and relevant studies, we also discuss suggestions for future research. Highlights: A cognitive level-based situational English vocabulary gaming approach is proposed. An experiment was conducted to evaluate the effectiveness of the new approach. The approach has been applied to a high school English course. The approach improved the students' learning achievement. Behavioral patterns were analyzed to explain the students' outcomes and perceptions.